Towards a general theory of good deal bounds - Tomas Björk; Irina Slinko (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
We consider an incomplete market in the form of a multidimensional Markovian factor model, driven by a general marked point process (representing discrete jump events) as well as by a standard multidimensional Wiener process. Within this framework we study arbitrage free good deal pricing bounds for derivative assets along the lines of Cochrane and Saa-Requejo, extending the CSR results to the point process case. As a concrete application we present numerical results for the classic Merton jump-diffusion model. As a by product of the general theory we also extend the Hansen-Jagannathan bounds for the Sharpe Ratio to the point process setting.
Keywords: G12; G13; 330; Incomplete markets; good deal bounds; financial derivatives; arbitrage pricing; Unvollkommener Markt; Finanzderivat; Optionspreistheorie